Hiilah: Antara Solusi Dan Manipulasi Dalam Hukum Islam - Ahmad . (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2018)
Islamic law is a set of laws born of Islam as a benchmark of the legality of a servant's deeds. There is no Muslim act as complex as anything apart from aspects of Islamic law. Thus, Islamic law will always be present to be a solution to the complexity of life's problems faced by humans. In reality, a Muslim not only finds the complexity of problematics in the aspects of the reality of life, but also occurs in the process of istinbath Islamic law itself. So in the process istinbath, Islamic law that should be a solution precisely be the manipulation of Islamic law itself. The complexity of the istinbath process of Islamic law itself can be found in a concept called hiilah.